JENIS KUPU-KUPU PAPILIONIDAE DI ZONA PENERIMA TAMAN HUTAN RAYA (TAHURA) RAJO LELO BENGKULU - Helmiyetti, Helmiyetti; Sari, Sri Puspita (Konservasi Hayati, 2019)
This study aims to determine the type of butterfly Papilionidae in the Receiver Zone of the Great Forest Park (GFP) Raja Lelo Bengkulu. The study was conducted in June- August 2017. Determination of the location of the study was conducted using purposive sampling and butterfly collection at each location using the roaming method. Butterfly collection is carried out at 08.00-10.00 WIB and continued in the afternoon at 15.00- 17.00 WIB, on sunny weather using insect nets. The butterflies obtained were taken to the Biology Laboratory of the Basic Science building, then stretched on a stretching board and dried in an oven at 40 0 C. Furthermore, the butterfly sample is identified by the butterfly identification book and grouped by Family, Genus and Species. The data obtained were analyzed descriptively. The results showed 7 species of Papilionidae butterflies, 74 individuals belonging to 4 genera. The types of butterflies obtained were Graphium agamemnon, Grapihum sarpedon, Pachliopta aristolochiae, Papilio polytes, Papilio memnon, Papilio palinurus, Troides helena.